Exploitation of Women in the Name of Capture Marriage Culture in Sumba in the Novel Women Who Cry to the Black Moon by Dian Purnomo - Faridhatun Nikmah; Agus Nuryatin; Mulyono (P3I UMSurabaya, 2024)
The culture of captive marriage that occurs in Sumba as depicted in the novel Women Who Cry to the Black Moon by Dian Purnomo. This cultural practice represents an injustice against women and creates stigma for victims who escape abduction. Using a qualitative descriptive method, the study highlights how captive marriage violates women's right to freedom and leads to exploitation in cultural contexts. Forms of exploitation identified in the novel include rape, human trafficking, and violence against women. The findings emphasize that these exploitative practices significantly impact victims, necessitating prevention efforts and protection from families, society, and the state to safeguard women's rights.